United Nations Partnerships With the Alcohol Industry - Leung JYY; Casswell S (Kerman University of Medical Sciences, 2026)
Background: The alcohol industry builds engagement with United Nations (UN) organisations to enhance its corporate image and influence policy, supported by the UN’s endorsement of public-private partnerships (PPPs). However, the extent of the alcohol industry’s relationships with the UN remains unclear due to limited reporting. Methods: We searched the websites of 57 UN-affiliated entities and 18 transnational alcohol corporations (TNACs) for evidence of partnerships or relationships between the UN and the alcohol industry. We summarised the UN entities and TNACs involved in formal partnerships, membership of alliances or stakeholder networks, financial contributions, sponsorship of programmes or projects, sponsorship of events, event participation, and personal relationships with conflicts of interest. Results: We identified examples of all the above relationships between various UN entities and the world’s largest TNACs, including an alcohol industry donation towards the World Health Organization (WHO) Foundation, which was created to maximise private sector donations to WHO. The focus of these engagements aligned closely with the alcohol industry’s corporate social responsibility (CSR) initiatives, including drink-driving prevention, education, sustainability, and philanthropy. These activities frequently involved support for low-and middle-income countries (LMICs) and women, which are emerging markets for the TNACs. Sponsorship and participation in intergovernmental events allowed the TNACs privileged access to policy-makers. Limited disclosure by UN entities meant that our findings provided an incomplete picture of relationships with the alcohol industry. Conclusion: The UN’s wide-ranging relationships with the TNACs highlight the power of these large corporations in building political influence and the UN’s failure to acknowledge the alcohol industry’s conflicting interests with health. These relationships undermine WHO’s mandate to promote health, placing the integrity and impartiality of the UN system at risk. On top of adequate resources from member states and enhanced transparency measures, the UN requires effective safeguards against alcohol industry influence, in line with those for the tobacco industry.
Keywords: Alcohol; Corporate Social Responsibility; Industry; Partnership; United Nations